Evaluation of the shear bond strength of the union between two CoCr-alloys and a dental ceramic - Pretti, Mariana [UNESP]; Hilgert, Edson; Bottino, Marco Antônio; Avelar, Rander Pereira (Journal Of Applied Oral Science : Revista Fob, 2004)
Introduction: Based on the importance of the integrity of the metal/ceramic interface, the purpose of this work was to evaluate the shear bond strength of the metal-ceramic union of two Co-Cr alloys (Wirobond C, Bego; Remanium 2000, Dentaurum) combined with Omega 900 ceramic (Vita Zahnfabrik). Material and Method: Eleven cylindrical matrixes were made for each alloy, and the metallic portion was obtained with the lost wax casting technique with standardized waxing of 4mm of height and of 4mm of diameter. The ceramic was applied according to the manufacturer's recommendations with the aid of a teflon matrix that allowed its dimension to be standardized in the same size as the metallic portion. The specimens were submitted to the shear bond test in an universal testing machine (EMIC), with the aid of a device developed for such intention, and constant speed of 0.5mm/min. Results and Conclusions: The mean resistance was 48.387MPa for Wirobond C alloy, with standard deviation of 17.718, and 55.956MPa for Remanium 2000, with standard deviation of 17.198. No statistically significant difference was observed between the shear strength of the two metal-ceramic alloys.

Introdução: Baseados na importância da integridade da interface metal-cerâmica, este trabalho tem como objetivo avaliar a resistência ao cisalhamento da união metal-cerâmica de duas ligas de Co-Cr (Wirobond C, Bego; Remanium 2000, Dentaurum) combinadas com a cerâmica Omega 900 (Vita Zahnfabrik). Materiais e Métodos: Foram confeccionados 11 corpos-de-prova cilíndricos para cada liga utilizada, sendo que a porção metálica foi obtida por fundição pela técnica da cera perdida, através de enceramentos padronizados com 4mm de altura por 4mm de diâmetro. A aplicação da cerâmica foi realizada segundo recomendações do fabricante, com auxílio de uma matriz de teflon que permitia sua padronização com as mesmas dimensões da porção metálica. Os corpos-de-prova foram submetidos ao ensaio de resistência ao cisalhamento em máquina de ensaios universal (EMIC), com auxílio de dispositivo desenvolvido para tal propósito, sob velocidade constante de 0,5mm/min. Reultados e Conclusões: As médias de resistência obtidas foram 48,387 MPa para a liga Wirobond C, com desvio padrão de 17,718, e 55,956 MPa para a Remanium 2000, com desvio padrão de 17,198. Após análise de variância foi possível observar que não há diferença estatisticamente significante entre os valores de resistência ao cisalhamento das duas ligas metalocerâmicas.
Avaliação da resistência ao cisalhamento da união entre duas ligas a base de CoCr e uma cerâmica
Keywords: Ceramics; Shear test; Alloys; Cerâmicas; Teste de cisalhamento; Ligas